Implementation of the Role and Function of the Village Consultative Body in the Implementation of Village Government in Tugu Village, Lelea District, Indramayu Regency - Senja Nirwana (Penerbit Hellow Pustaka, 2025)
In line with the development and progress of society, as well as the high demands of society in various fields of life, it is certainly the task of the government, including the village government as the public servant closest to its people to answer the challenges of various changes that are implemented through thinking, acting and doing things rationally, professionally and accountably according to the main tasks, functions and authorities and responsibilities of the organization - village government. The Village Consultative Body (BPD) as an element of the Village Government organizer has the function of establishing Village Regulations together with the Kuwu, and accommodating and channeling community aspirations. The BPD and the Village Government have a partnership and coordinative relationship in order to carry out the function of establishing Village Regulations, accommodating and channeling community aspirations. In general, the implementation of the role and function of the BPD in Tugu Village has been going quite well, but still needs to be improved, so that it can support the implementation of village government effectively